2018
DOI: 10.1021/acs.energyfuels.7b03658
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Oil Viscosity of Sisal Residue: Process and Temperature Influence

Abstract: The viscosity of sisal residue bio-oil was evaluated using the variation of the operational conditions of the fast pyrolysis process in a fluidized bed. The bio-oil was produced in a pilot plant from tests that were designed using the technique of experimental design. In this work, the effect of the flow rate of the inert gas (N 2 ), the biomass mass flow rate, and the reaction temperature on the viscosity at the shear rates of 40 and 75 s −1 was investigated. The lowest viscosity was obtained when the N 2 flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…When the influence of the waste material on the viscosity was compared, it was observed that lower viscosity was obtained for the co-pyrolysis of GS and PS than for the GS and WT mixtures using the same catalyst, Carmeuse, indicating that this polymer, PS, improved the quality of the oil obtained versus the WT. As the bio-oil viscosity is widely dependent on the feedstock and pyrolysis conditions, 42,43 this improvement in the viscosity for the co-pyrolysis experiments could be explained based, on the one hand, on the feedstock (PS consists of volatile matter and almost no fixed carbon (Table 1), whereas that WT is made of styrene−butadiene copolymer, natural rubber, and polybutadiene) and, on the other hand, on the nature and chemical composition of the bio-oils as shown in the next paragraphs.…”
Section: Resultsmentioning
confidence: 99%
“…When the influence of the waste material on the viscosity was compared, it was observed that lower viscosity was obtained for the co-pyrolysis of GS and PS than for the GS and WT mixtures using the same catalyst, Carmeuse, indicating that this polymer, PS, improved the quality of the oil obtained versus the WT. As the bio-oil viscosity is widely dependent on the feedstock and pyrolysis conditions, 42,43 this improvement in the viscosity for the co-pyrolysis experiments could be explained based, on the one hand, on the feedstock (PS consists of volatile matter and almost no fixed carbon (Table 1), whereas that WT is made of styrene−butadiene copolymer, natural rubber, and polybutadiene) and, on the other hand, on the nature and chemical composition of the bio-oils as shown in the next paragraphs.…”
Section: Resultsmentioning
confidence: 99%
“…Bio-oil of the sisal residue has characteristics of heavy bio-oil (Figure ), the formation of which derived partially from lignin, which is the most abundant polymer of the sisal residue (Table ). The bio-oil yields have been reported in the literature as light and heavy fractions. Table shows that the heavy bio-oil yield varied between 14.3% and 79%, depending on the type of biomass and variation of pyrolysis temperature. Although the higher yields of the sisal residue bio-oil are in the range of heavy fractions, the absence of the aqueous phase is not common in relation to those produced by another biomass.…”
Section: Resultsmentioning
confidence: 99%
“…26 This effect is in agreement with the surface behavior shown in Figure 6, that even at temperatures above 500 °C, bio-oil production increases with increasing biomass flow rate due to the decrease in the solid-to-solid heat rate. In addition, increasing the biomass flow rate increased the residence time of the organic molecules, 43 contributing to the increase and decrease of the yields of heavy and light fractions, respectively. 44 Bio-oil of the sisal residue has characteristics of heavy bio-oil (Figure 7), the formation of which derived partially from lignin, 44 which is the most abundant polymer of the sisal residue (Table 2).…”
Section: Energy and Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the dependent variable S (ou Uff) is complex, and the interaction effects must be teased out using statistical analysis [18,19]. The response surface methodology (RSM) consists of graphically representing each parameter's influence and their interactions in the results, which can be used to derive the ideal conditions to improve the process [18].…”
Section: Fig 3 Fluidization With Segregationmentioning
confidence: 99%